Hazra chicken: A precious germplasm in need of immediate scientific intervention - SHARMA, REKHA; SHARMA, HIMANI; AHLAWAT, SONIKA; BARIK, N; SINGH, P K; TANTIA, M S (The Indian Journal of Animal Sciences, 2017)
Indian poultry diversity is still largely unexplored, even though more than half of the germplasm is endangered. The present study was planned to ascertain the genetic diversity of local poultry population of Odisha (Hazra) using 25 Simple Sequence Repeat markers. All the loci were retained for diversity analysis due to their behavior as neutral markers in this population. Hazra chicken population was found to host a very high level of diversity. This conclusion is based on the large number of alleles observed across loci (average14.96, range 6-21), and by the high expected heterozygosity (average 0.80, range 0.50-0.92). In spite of high within-breed variation, signatures of inbreeding were detected by the FIS index, which was positive (0.218±0.03) in the population. Hazra chicken population presented the highest heterozygote deficiency as compared to all the 17 recognized poultry breeds of India. Nonsignificant heterozygote excess on the basis of infinite allele model (IAM) along with a normal ’L’-shaped distribution of mode-shift analysis test, indicated an absence of bottleneck. In summary, molecular data conclude that Hazra population possesses a very interesting pool of chicken genetic resources due to their high genetic diversity. Increased level of inbreeding is indicating that flock management and reproduction strategies deserve attention.